Retinoic Acid Deficiency Underlies the Etiology of Midfacial Defects. (June 2022) - Wu, Y.; Kurosaka, H.; Wang, Q.; Inubushi, T.; Nakatsugawa, K.; Kikuchi, M.; Ohara, H.; Tsujimoto, T.; Natsuyama, S.; Shida, Y.; Sandell, L.L.; Trainor, P.A.; et al.
Embryonic craniofacial development depends on the coordinated outgrowth and fusion of multiple facial primordia, which are populated with cranial neural crest cells and covered by the facial ectoderm. Any disturbance in these developmental events, their progenitor tissues, or signaling pathways can result in craniofacial deformities such as orofacial clefts, which are among the most common birth defects in humans. In the present study, we show that Rdh10 loss of function leads to a substantial reduction in retinoic acid (RA) signaling in the developing frontonasal process during early embryogenesis, which results in a variety of craniofacial anomalies, including midfacial cleft and ectopic chondrogenic nodules. Elevated apoptosis and perturbed cell proliferation in postmigratory cranial neural crest cells and a substantial reduction in Alx1 and Alx3 transcription in the developing frontonasal process were associated with midfacial cleft in Rdh10 -deficient mice. More important, expanded Shh signaling in the ventral forebrain, as well as partial abrogation of midfacial defects in Rdh10 mutants via inhibition of Hh signaling, indicates that misregulation of Shh signaling underlies the pathogenesis of reduced RA signaling-associated midfacial defects. Taken together, these data illustrate the precise spatiotemporal function of Rdh10 and RA signaling during early embryogenesis and their importance in orchestrating molecular and cellular events essential for normal midfacial development.